Biomechanics of increased spin velocity of flying discs during forehand throws by skilled and unskilled throwers - Sasakawa, K.; Umegaki, K.; Sakurai, S. (Journal of Sports Sciences, 2018)
We aimed to assess the relationship between throwing distance and kinematic release parameters of the flying disc in unskilled throwers, and to assess the relationship between kinetic variables acting on flying discs and the change in spin velocity during long forehand throws by skilled and unskilled throwers. Ten skilled and eleven unskilled throwers performed throws at maximum effort. Reflective marker positions on the disc and body were recorded with a 3D motion capture system during the throws to derive kinematic variables of a disc and kinetic variables acting on the disc. The analysis interval was from maximum external shoulder rotation to disc release. Significant correlations were observed between the throwing distance and spin velocity in skilled (r = 0.722, P < 0.05) and unskilled throwers (r = 0.794, P < 0.01), between the change in spin velocity and the angular impulse of moments of force, in unskilled throwers (r = 0.703, P < 0.05), and between the change in spin velocity and the angular impulse of torque among skilled throwers (r = 0.680, P < 0.01). Therefore, a strategy for increasing spin velocity in unskilled throwers could be used to generate a larger torque, similar to that observed in skilled throwers.The purpose of this study was to determine hip joint kinetics during a table tennis topspin forehand, and to investigate the relationship between the relevant kinematic and kinetic variables and the racket horizontal and vertical velocities at ball impact. Eighteen male advanced table tennis players hit cross-court topspin forehands against backspin balls. The hip joint torque and force components around the pelvis coordinate system were determined using inverse dynamics. Furthermore, the work done on the pelvis by these components was also determined. The peak pelvis axial rotation velocity and the work done by the playing side hip pelvis axial rotation torque were positively related to the racket horizontal velocity at impact. The sum of the work done on the pelvis by the backward tilt torques and the upward joint forces was positively related to the racket vertical velocity at impact. The results suggest that the playing side hip pelvis axial rotation torque exertion is important for acquiring a high racket horizontal velocity at impact. The pelvis backward tilt torques and upward joint forces at both hip joints collectively contribute to the generation of the racket vertical velocity, and the mechanism for acquiring the vertical velocity may vary among players.